Cystitis due to Blastoschizomyces Capitatus Successfully Treated with Fluconazole: A Case Report - Al Demour, Saddam; Alrabadi, Adel; Haddad, Ra’ed; Tarawneh, Emad; Bakri, Faris (Jordan Medical Journal, 2018)
The incidence of fungal urinary tract infections has been increasing and is usually linked with the use of systemic chemotherapy, use of immunosuppressive medications, and overuse of antibiotics. Noncandida urinary tract infections are uncommon. Blastoschizomyces capitatus is an emerging invasive infection in immunosuppressed patients. Urinary infections with this pathogen are rarely reported. Here, we present a case of a diabetic female patient with a urinary tract infection caused by this pathogen. The infection was successfully treated with fluconazole therapy.